2015
DOI: 10.1007/s00586-015-4140-6
|View full text |Cite
|
Sign up to set email alerts
|

Duration-dependent influence of dynamic torsion on the intervertebral disc: an intact disc organ culture study

Abstract: Our result suggests that load duration thresholds exist in both torsion and compression with an optimal load duration capable of promoting matrix synthesis and overloading can be harmful to disc cells. Future research is required to evaluate the specific mechanisms for these observed effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Similar to numerous previous studies [36,37], we found a long-term load duration decreased the macromolecule (aggrecan and collagen II) expression and matrix biochemical content (GAG and HYP). Furthermore, the expression of specific markers in juvenile NP cells was also down-regulated in the long-term load duration group.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to numerous previous studies [36,37], we found a long-term load duration decreased the macromolecule (aggrecan and collagen II) expression and matrix biochemical content (GAG and HYP). Furthermore, the expression of specific markers in juvenile NP cells was also down-regulated in the long-term load duration group.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the architecture of the AF may act to protect collagen fibers from failure and reduce shear stresses at the AF‐endplate interface, which is a common site for disc failure under large rotation angles . It should be noted that while the AF structure may protect the disc from catastrophic failure, high local shear stresses may still initiate tissue remodeling towards the degenerative cascade …”
Section: Discussionmentioning
confidence: 99%
“…Our experiments were performed with excised discs constrained by porous metal platens, a common boundary condition in organ culture systems . This condition was chosen for the present study to allow freezing and cryosectioning of the discs with minimal handling after injection, which was presumed to affect dye distribution.…”
Section: Discussionmentioning
confidence: 99%
“…26 The fluorescent dye measurements ( Figure 3 Our experiments were performed with excised discs constrained by porous metal platens, a common boundary condition in organ culture systems. [27][28][29] This condition was chosen for the present study to allow freezing and cryosectioning of the discs with minimal handling after injection, which was presumed to affect dye distribution. Pilot studies found no differences in either peak pressure or rate of depressurization between excised discs and discs still attached to adjacent vertebrae.…”
Section: Discussionmentioning
confidence: 99%